A Review of Clinical Practice Guidelines for Physiotherapy Management of Patients with Non-Specific Low Back Pain - Harikrishnan Ranganathan; Devinder Kaur Ajit Singh (Medsci Publications, 2024)
Background: Despite the availability of various clinical practice guidelines (CPGs) offering evidence-based recommendations, there exists a global diversity in physiotherapy practices for managing patients with non-specific low back pain (NSLBP). In this review, we aim to critically appraise and map the current evidence regarding physiotherapy management for patients with NSLBP. Methods: A search strategy was formulated and searched in MEDLINE, Scopus, EBSCOhost, PEDro and Google Scholar between 2013 and 2023 in English. Critical appraisal was performed using International Centre for Allied Health Evidence (iCAHE) guideline checklist. Results: A total of 12 CPGs met the selection criteria were synthesised. Exercise therapy, physical activity and manual therapy were consistently recommended for patients with NSLBP across most guidelines, irrespective of symptom duration. Cognitive-behavioural therapy was frequently advised for those with chronic NSLBP. However, notable absences of recommendations for electrotherapy, mechanical traction, bed rest, and lumbar corsets in NSLBP management. Moreover, emerging treatments such as shock wave therapy and cognitive-functional therapy were not extensively addressed in the guidelines. Conclusion: Multimodal and active forms of physiotherapy management were predominantly recommended in most of the guidelines. However, there is a clear necessity for updated CPG that effectively integrate biopsychosocial approaches into the management of patients with NSLBP.